Future Challenges in Pediatric and Neonatal Sepsis: Emerging Pathogens and Antimicrobial Resistance - Folgori, Laura; Bielicki, Julia (Journal of Pediatric Intensive Care, 2019)
The incidence of severe infections caused by multidrug-resistant (MDR) pathogens is currently rising worldwide, and increasing numbers of neonates and children with serious bloodstream infections due to resistant bacteria are being reported. Severe sepsis and septic shock due to gram-negative bacteria represent a significant cause of morbidity and mortality, and contribute to high health care costs. Antimicrobial resistance among Enterobacteriaceae represents a major problem in both health care-associated and community-acquired infections, with extended-spectrum β-lactamases (ESBLs) and carbapenem-resistant Enterobacteriaceae (CRE) now presenting the main threat. These infections in adult populations have been associated with poor clinical outcomes, but very limited data have been published so far about risk factors and clinical outcome of ESBL-associated and CRE sepsis in the pediatric population. The treatment of these infections in neonates and children is particularly challenging due to the limited number of available effective antimicrobials. Evidence-based use of new and older antibiotics based on both strategic and regulatory clinical trials is paramount to improve management of these severe infections in neonates and children.
Keywords: sepsis; pediatrics; neonate; drug resistance; bacterial; gram-negative bacteria